The Role of Customary Law in Natural Resource Management: A Comparative Study between Indonesia and Australia - Buana, Andika Prawira; Mamonto, Moch Andry Wikra Wardhana (Manunggal Halim Jaya, 2023)
Natural resource management is crucial for sustainable development, especially in regions abundant in biodiversity and natural assets. Nations worldwide face the challenge of managing their resources effectively while promoting economic growth, social justice, and environmental conservation. Customary law plays a significant role in resource governance, particularly in countries like Indonesia and Australia, where indigenous communities have deep-rooted connections to the land and its resources. This comparative study explores the role of customary law in natural resource management in Indonesia and Australia. Both countries possess diverse ecosystems and substantial indigenous populations, offering valuable insights into the interaction between customary and state legal systems in resource governance. In Indonesia, customary law, known as adat, influences resource management practices, albeit with variations in recognition and integration into formal legal frameworks. Conversely, in Australia, the colonization process has disrupted traditional governance structures, leading to ongoing struggles for indigenous rights and recognition. By examining case studies, legal frameworks, and policy initiatives in both countries, this study aims to identify challenges and opportunities for integrating customary law into broader governance frameworks and promoting more equitable and sustainable resource management practices. Additionally, this comparative analysis contributes to scholarly debates on the role of customary law in contemporary legal systems and its implications for environmental governance, indigenous rights, and social justice. Interdisciplinary perspectives from legal studies, anthropology, environmental science, and development studies offer valuable insights for policymakers, practitioners, and indigenous communities striving for more inclusive and effective resource management approaches.